2015
DOI: 10.3390/proteomes3030132
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Hematopoietic Stem/Progenitor Cells after a Whole Body Exposure of CBA/CaJ Mice to Titanium (48Ti) Ions

Abstract: Myeloid leukemia (ML) is one of the major health concerns from exposure to radiation. However, the risk assessment for developing ML after exposure to space radiation remains uncertain. To reduce the uncertainty in risk prediction for ML, a much increased understanding of space radiation-induced changes in the target cells, i.e., hematopoietic stem/progenitor cells (HSPCs), is critically important. We used the label-free quantitative mass spectrometry (LFQMS) proteomic approach to determine the expression of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Rithidech et al . showed that the NF-κB and MAPKs pathways in hematopoietic stem cells play an essential role in the response to acute whole-body exposure to a low dose 34 . IL6 expression is induced by NF-κB 35 , suggesting that the NF-κB pathway in ODIC is activated even at a lethal dose of IR exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Rithidech et al . showed that the NF-κB and MAPKs pathways in hematopoietic stem cells play an essential role in the response to acute whole-body exposure to a low dose 34 . IL6 expression is induced by NF-κB 35 , suggesting that the NF-κB pathway in ODIC is activated even at a lethal dose of IR exposure.…”
Section: Discussionmentioning
confidence: 99%